Analisis Perbedaan Kinerja Bank Syariah dan Bank Konvensional - Rahmadita Karunia; Risyda Tazkiyatun Nufus; Tiara Anggita Sari; Hawwa Syifa Azzahra; Aulia Rahma Putri Ananda Realita Islami; Miya Ulya Sari; Muhamad Panji Satria; Aulia Rahma Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This material provides an in-depth overview of the fundamental distinctions between Islamic banks and conventional banks, covering their underlying principles, contract types, operational mechanisms, legal frameworks, and organizational structures. Islamic banks operate based on Islamic values derived from the Qur’an, Hadith, and the rulings of the National Sharia Council (DSN-MUI), emphasizing strict prohibitions on riba, gharar, and maysir. Contracts such as wadiah, mudharabah, musyarakah, murabahah, ijarah, salam, and istishna’ are applied to promote fairness and profit-sharing. In contrast, conventional banks rely on positive law and interest-based systems as their primary source of income. Legally, Islamic banks are supervised by the Sharia Supervisory Board (DPS) to ensure compliance with sharia principles, while conventional banks adhere solely to general financial regulations set by authorities like the Financial Services Authority (OJK) and Bank Indonesia. The operations of Islamic banks include fund mobilization, financing, and financial services without the use of interest, whereas conventional banks earn revenue from the interest spread between deposits and loans. Although both bank types share a similar organizational structure, Islamic banks incorporate an additional layer of sharia oversight. Overall, Islamic banks aim to balance profitability with ethical and spiritual values (falah), while conventional banks primarily focus on maximizing financial returns. This material highlights Islamic banking as an ethical alternative within modern financial practices, promoting justice, sustainability, and broader economic well-being.